Basic ventilatory setting and monitoring - Kundan Mittal; Vinayak Patki (Wolters Kluwer Medknow Publications, 2018)
Mechanical ventilation both invasive and non-invasive are key requirement of any high dependency and intensive care units to provide respiratory support in emergency as well as electively. Most of the time trained residents are not available and one has to depend on trained staff and respiratory physiotherapist. One may not be well versed with advanced mode and graphics but must know basics. Thus, it is essential to understand machine, basics ventilatory settings, monitoring parameters on ventilator, and weaning criteria from mechanical ventilation.